Chimeric Antigen Receptor (CAR) therapy for multiple myeloma. (20th January 2016) - Atanackovic, Djordje; Radhakrishnan, Sabarinath V.; Bhardwaj, Neelam; Luetkens, Tim
Summary: The introduction of chimeric antigen receptor (CAR)‐modified T cells has revolutionized immunotherapy and cancer treatment as a whole. However, so far, clinical efficacy has only been demonstrated for CD19‐positive B cell lymphomas. For Multiple Myeloma (MM), the second most common haematological malignancy, there are currently no clinical results supporting the usefulness of the adoptive transfer of CAR‐modified T cells. This might be related to the fact that an ideal surface target has not yet been identified or the presence of strong local immunosuppression in the tumour microenvironment, which is a hallmark of MM. In this review, we provide a comprehensive overview of promising target molecules for CAR T cell approaches in MM and we outline a number of ways in which the local immunosuppression in MM can be overcome. By providing a strategy for the design of CAR T cell treatments for MM we hope to transform this new therapeutic approach into a valuable tool within the therapeutic armamentarium for MM.